The Effect of Workload, Work-Life Balance, and Burnout on Job Satisfaction with the Mediation of Digital Transformation Readiness Among Generation Z Employees in the Mining Sector in Jakarta - Leoni Angela Fortunata; Liem Bambang Sugiyanto (International Journal Labs, 2026)
This study aims to examine the effect of workload, work-life balance, and burnout on job satisfaction, with digital transformation readiness as a mediating variable, among Generation Z employees in the mining sector in Jakarta. This research employs a quantitative approach using the SEM-PLS method via SmartPLS, with data collected from 155 respondents using a Likert-scale questionnaire. The results indicate that digital transformation readiness has the strongest and most significant positive effect on job satisfaction. Workload, work-life balance, and burnout do not directly influence job satisfaction. However, digital transformation readiness significantly mediates the relationship between work-life balance and burnout and job satisfaction, while it does not mediate the relationship between workload and job satisfaction. These findings highlight the strategic role of digital transformation readiness in enhancing job satisfaction among Generation Z employees. Practically, the results provide insights for mining companies in strengthening digital capabilities, supporting employee adaptability to technological change, and sustaining work-life balance policies. Nevertheless, this study is limited to Generation Z employees in the mining sector in Jakarta. Future research is recommended to examine similar variables among site-based mining employees in order to obtain a more comprehensive understanding of employee work behaviour.